CFD (Computational Fluid Dynamic) untuk menganalisis head loss akibat perubahan diameter - Nur Hayati; Adi Purwanto; Erwan Muladi (Badan Kerja Sama Teknik Mesin Indonesia, 2023)
Piping systems with many supporting components are used to drain water. Connections or elbows result in head loss, namely the loss of flow in the system. Headloss is the loss of flow energy which is significantly affected by flow velocity. This study aims to analyze head loss due to variations in elbow diameter. The elbows used have diameters of 1, 2, 4, and 6 inch. Based on the simulation results and the results of nomograph calculations using the ASME B16.9 B16.28 standard, it can be seen that head loss decreases with increasing elbow diameter. The simulation results show similar results to the calculations from the nomograph.